2017
DOI: 10.14710/jitaa.42.4.247-254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some insects as potential feed ingredients for ruminants: chemical composition, in vitro rumen fermentation and methane emissions

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengevaluasi kandungan nutrien, fermentasi rumen, kecernaan dan emisi metana secara in vitro sejumlah serangga yakni jangkrik (JFC), ulat hongkong (MW) dan larva black soldier fly berumur 1 dan 2 minggu (BSF1 dan BSF2). Sampel serangga dikeringkan pada suhu 60 o C selama 24 jam, kemudian digiling berukuran 1 mm. Sampel yang telah digiling kemudian dianalisis kandungan nutriennya serta diuji secara in vitro. Inkubasi in vitro dilakukan pada water bath pada suhu 39ºC selama … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 30 publications
8
55
1
5
Order By: Relevance
“…The ruminal IVTDMD of untreated BSFL was high (0.88), indicating its potential as a digestible component in the ruminant diet. In contrast, Jayanegara et al [30] found a lower IVTDMD in BSFL (<0.56) and other insect species (Jamaican field cricket-0.64, and mealworm-0.60). As in the case of the monogastric ATTD, TP did not affect (p > 0.05) the IVTDMD.…”
Section: In Vitro Digestibilitymentioning
confidence: 82%
See 1 more Smart Citation
“…The ruminal IVTDMD of untreated BSFL was high (0.88), indicating its potential as a digestible component in the ruminant diet. In contrast, Jayanegara et al [30] found a lower IVTDMD in BSFL (<0.56) and other insect species (Jamaican field cricket-0.64, and mealworm-0.60). As in the case of the monogastric ATTD, TP did not affect (p > 0.05) the IVTDMD.…”
Section: In Vitro Digestibilitymentioning
confidence: 82%
“…BSFL showed a high content of relevant macro (Ca, P, K, Mg) and micro minerals (Mn, Fe, Zn), with a Ca/P ratio of 4.2. Ca level, the major mineral of BSFL, is dependent on the substrate and tends to increase in the pre-pupae and pupae stage [30]. The calcium content of BSFL found in the present study was higher (18.5 g/kg DM) than in previous studies using a similar substrate (5.36 g/kg [31]; 1.70 g/kg [22]) but lower than common values observed in BSFL (50-86 g/kg [3]).…”
Section: Discussionmentioning
confidence: 99%
“…The chemical analysis included proximate analysis, i.e.,, dry matter (DM), ash, organic matter (OM), CP, ether extract (EE), crude fiber, and nitrogen-free extract [ 16 ], Van Soest’s analysis, i.e., neutral detergent fiber (NDF) and acid detergent fiber (ADF) [ 17 ], and insoluble CP determination, i.e., neutral detergent insoluble CP (NDICP) and acid detergent insoluble CP (ADICP) [ 18 ]. Chemical composition determination of the individual feed materials was performed in duplicate, and the results had been published elsewhere [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Apart from their high protein contents, insects contain relatively good and balance amino acid profiles [ 2 ] and have been fed to some animal species particularly the monogastrics such as fish, poultry, and swine [ 3 ]. Insect species that have been evaluated as feed resources included locust, grasshopper, cricket, silkworm, house fly maggot [ 4 ], mealworm [ 5 , 6 ], and black soldier fly (BSF) larvae [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maggot (Hermetia illucens) atau larva black soldier fly dapat menjadi salah satu sumber protein alternatif dalam ransum unggas. Menurut Jayanegara et al (2017), tepung maggot (Hermetia illucens) mempunyai kandungan protein kasar sebesar 44,9%, lemak kasar sebesar 29,1%, serat kasar sebesar 16,4%, dan abu sebesar 8,1%. Kandungan nutrisi maggot (Hermetia illucens) berupa protein kasar memiliki persentase yang cukup tinggi dan hal tersebut mengindikasikan bahwa maggot (Hermetia illucens) memiliki potensi besar untuk menggantikan MBM.…”
unclassified